The Freedom of Expression and the Right to Information – Fundamental Rights Affected by Fake News? - Niță, Anca Jeanina (Technium Social Sciences Journal, 2022)
The present paper seeks to function as an incentive for debate on the extent in which – in the context of a disturbing expansion of the fake news phenomenon – a law of the press is needed in Romania. It invokes the interdependency between the right to information and the freedom of expression, it presents the constitutional requirements concerning these fundamental rights, including those about restricting their exercise in exceptional circumstances. It observes the duties of the actors belonging to the mass media ecosystem as provided in the Recommendation CM/Rec(2011)7 of the Council of Europe and it invokes the relevant case law of the European Court of Human Rights. Without arrogating solutions, it argues that a legislative intervention may well degenerate into an abuse against the freedom of expression, that a law of the press cannot completely protect against disinformation, whereas the development of public policies – in which all actors responsible for fighting the fake news phenomenon ought to be engaged – is not only welcome, but necessary.